Ballistic Transport at the Nanometric Inhomogeneities in Au/Nb:SrTiO3 Resistive Switches. Issue 3 (10th March 2014) - Gerbi, Andrea; Buzio, Renato; Gadaleta, Alessandro; Anghinolfi, Luca; Caminale, Michael; Bellingeri, Emilio; Siri, Antonio Sergio; Marré, Daniele
<x xml:space="preserve">Abstract</x> Novel ballistic electron emission microscopy experiments are reported, aimed to directly visualize and quantify the local inhomogeneities of the effective Schottky barrier height on Au/Nb:SrTiO3 Schottky junctions dominated by interfacial resistance switching effects. The voltage‐dependent variation of the local barrier height of the nanometric patches could explain the non‐ideal behaviour of the resistance switching effects in transition‐metal oxide cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>